-55+3x=85-x

Simple and best practice solution for -55+3x=85-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -55+3x=85-x equation:



-55+3x=85-x
We move all terms to the left:
-55+3x-(85-x)=0
We add all the numbers together, and all the variables
3x-(-1x+85)-55=0
We get rid of parentheses
3x+1x-85-55=0
We add all the numbers together, and all the variables
4x-140=0
We move all terms containing x to the left, all other terms to the right
4x=140
x=140/4
x=35

See similar equations:

| 12−0.8(x+15)=0.4x+6 | | -7x-5=-10x+26 | | 2x3-3x2=0 | | 14x-31=12x+47 | | 2x+39+1+90=180 | | 10x=560 | | 6x-9-9x=15+4x-3x | | –2u−7=–u | | (x+40)+(3x-80)=180 | | 12x-29=10x-19 | | 5+3|10−4x|=20 | | 2(x-1)+6=3+2x-10 | | 10+10+d+d=10d | | 12+3w=27 | | 5/8x=15/2 | | 14x-91=69+4x | | 66=–11y | | 5+3∣10−4x∣=20 | | -59/60=1/6x+9/5x | | 10/15+9x/5=31/15 | | 6(n+5)=3(n+16 | | 11x-70=5x+20 | | -10(s+88)=30 | | 0.6x+76=x | | -3x+-17=-1(17+3x) | | −1/4s−3/2=3/4 | | -4-5m=-4m-9 | | 3/5(t+13)=-3(3-t) | | -5x+7=9-5x | | 19x+3=130 | | x+10/5=-12 | | -5x+7=9–5x |

Equations solver categories